Medial entorhinal cortex commissural input regulates the activity of spatially and object-tuned cells contributing to episodic memory - Caputi, Antonio; Liu, Xinghua; Fuchs, Elke C.; Liu, Yu-Chao; Monyer, Hannah (Neuron, 2022)
Extensive interhemispheric projections connect many homotopic brain regions, including the hippocampal formation, but little is known as to how information transfer affects the functions supported by the target area. Here, we studied whether the commissural projections connecting the medial entorhinal cortices contribute to spatial coding, object coding, and memory. We demonstrate that input from the contralateral medial entorhinal cortex targets all major cell types in the superficial medial entorhinal cortex, modulating their firing rate. Notably, a fraction of responsive cells displayed object tuning and exhibited a reduction in their firing rate upon the inhibition of commissural input. In line with this finding are behavioral results that revealed the contribution of commissural input to episodic-like memory retrieval.
Gesehen am 14.02.2023
Available online 8 September 2022, Version of Record 19 October 2022